Effect of Bicarbonate Supplementation on Renal Function and Nutritional Indices in Predialysis Advanced Chronic Kidney Disease - Jeong, Jiwon; Kwon, Soon Kil; Kim, Hye-Young (Electrolyte & blood pressure : E & BP, 2014)
Current practice guidelines recommend alkali therapy in patients with chronic kidney disease (CKD) and metabolic acidosis to prevent complications. This study aims to investigate the effect of oral sodium bicarbonate supplementation on the progression of renal function and nutritional indices in patients with predialysis advanced CKD. Forty patients with predialysis stage 5 CKD(estimated glomerular filtration rate, eGFR <15mL/min per 1.73m(2)) and 40 patients with stage 4 CKD (eGFR 15 to 30mL/min per 1.73m(2)) who had a total CO2 less than 22mEq/L were assigned into the bicarbonate treatment group or control group for 12 months. In stage 4 CKD, there were significant differences in the changes of eGFR during the study between the treatment group and the control group (-2.30±4.49 versus -6.58±6.32mL/min/1.73m(2), p<0.05). However, in stage 5 CKD, there were no significant differences in the change of eGFR during the study between the two groups (-2.10±2.06 versus -3.23±1.95mL/min/1.73 m(2)).There were no significant differences in the changes of nutritional indices such as albumin, prealbumin, transferrin, total lymphocyte count (TLC), and Ondodera's prognostic nutritional index (OPNI) during the study between the two groups. In stage 5 CKD, there were significant differences in the changes of TLC and OPNI between the two groups. In conclusion, our results demonstrate that bicarbonate supplementation slows the rate of decline of renal function in stage 4 CKD and improves nutritional indices in stage 5 CKD. Alkali therapy in advanced CKD may have beneficial effect on renal function and malnutrition.